1997
DOI: 10.1128/jb.179.21.6824-6830.1997
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a streptomycete leaderless mRNA encoding chloramphenicol acetyltransferase in Escherichia coli

Abstract: The chloramphenicol acetyltransferase (cat) gene from Streptomyces acrimycini encodes a leaderless mRNA. Expression of the cat coding sequence as a leaderless mRNA from a modified lac promoter resulted in chloramphenicol resistance in Escherichia coli. Transcript mapping with nuclease S1 confirmed that the 5 end of the cat message initiated at the A of the AUG translational start codon. Site-directed mutagenesis of the lac promoter or the cat start codon abolished chloramphenicol resistance, indicating that E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…PCR amplification with Pfu DNA polymerase (Stratagene), pIU1041 (Wu and Janssen, 1997) as template, a downstream primer (5Ј-ACGCTCATCGATAATTTCACC-GCC-3Ј), and each of the following upstream primers was used to prepare blunt-ended DNA fragments of cI-lacZ with the indicated 5Ј terminal start codons: AUG: 5Ј-ATGAGCA-CAAAAAAGAAACCATTAAC-3Ј; UAG: 5Ј-TAGAGCACAA-AAAAGAAACCATTAAC-3Ј; UAUAG: 5Ј-TATAGAGCACA-AAAAAGAAACCATTAAC-3Ј. The reaction products were cloned separately into a plasmid containing a lacUV5 promoter such that transcription was expected to initiate at the first position of the cloned fragment or a plasmid where the cloning site mapped to the translational start site of a modified leadered lacZ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplification with Pfu DNA polymerase (Stratagene), pIU1041 (Wu and Janssen, 1997) as template, a downstream primer (5Ј-ACGCTCATCGATAATTTCACC-GCC-3Ј), and each of the following upstream primers was used to prepare blunt-ended DNA fragments of cI-lacZ with the indicated 5Ј terminal start codons: AUG: 5Ј-ATGAGCA-CAAAAAAGAAACCATTAAC-3Ј; UAG: 5Ј-TAGAGCACAA-AAAAGAAACCATTAAC-3Ј; UAUAG: 5Ј-TATAGAGCACA-AAAAAGAAACCATTAAC-3Ј. The reaction products were cloned separately into a plasmid containing a lacUV5 promoter such that transcription was expected to initiate at the first position of the cloned fragment or a plasmid where the cloning site mapped to the translational start site of a modified leadered lacZ.…”
Section: Methodsmentioning
confidence: 99%
“…The widespread occurrence of leaderless mRNA suggests that translation of leaderless mRNA might represent a fundamental capability of all translation systems. In possible support of this, it has also been shown that leaderless mRNAs are translated in heterologous hosts (Janssen, 1993;Wu and Janssen, 1997).…”
Section: Introductionmentioning
confidence: 91%
“…Total RNA was isolated from the parental 19606 strain and the Bfm17 and Bfm273 mutants as described previously (Wu & Janssen, 1997), and each RNA sample was further purified using the Qiagen RNeasy Total RNA Isolation System including the RNase-free DNase incolumn treatment, before amplification using one-step RT-PCR (Qiagen). The primers 1978 (59-TACGTGGTATCGAATACG-39) and2036 (59-ATTGCTTGCATCGTAACG-39) (Fig.…”
mentioning
confidence: 99%
“…The transcription of the bau genes was tested by RT-PCR analysis using total RNA isolated from bacteria grown under iron-limiting conditions as described before (Wu & Janssen, 1997). The RNA samples were treated with RNase-free DNase I (Roche) and used with an RT-PCR commercial kit (Qiagen) under the conditions suggested by the manufacturer.…”
mentioning
confidence: 99%